Frequency of Primary Infertility with PCOS among Women Aged 25 to 30 Years in Tertiary Care Hospitals Quetta - Zahoor, Farhat; Azam, Saima; Haroon, Zahida; Mengal, Safia; Ghilzai, Gulnar (Biological and Clinical Sciences Research Journal, 2025)
A significant worldwide health issue, infertility has detrimental psychological and societal effects. With 3.5% of cases being primary infertility, Pakistan has one of the highest rates of infertility in South Asia. Anovulatory infertility is primarily caused by polycystic ovarian syndrome (PCOS), the most common endocrine condition affecting women of reproductive age. Nevertheless, there is still a lack of information about infertility in Balochistan linked to PCOS. Objective: to ascertain the prevalence of PCOS-related primary infertility in women between the ages of 25 and 30 who visit Quetta’s tertiary care facilities. Methods: This cross-sectional descriptive study was carried out in Quetta’s tertiary care hospitals’ obstetrics and gynecology departments. Through non-probability convenience sampling, 200 married women between the ages of 25 and 30 who met the Rotterdam criteria for PCOS and main infertility were included. A standardized, pre-tested questionnaire that covered socio demographic information, menstrual and reproductive history, PCOS clinical symptoms, ultrasound findings, and psychosocial impact was used to gather data. SPSS version 26 was used for data analysis. While chi-square and independent t-tests were used to evaluate relationships, descriptive statistics were computed. Results: On ultrasonography, polycystic ovaries were seen in nearly half of the individuals (49.5%), and irregular menstruation was very common (oligomenorrhea in 28% and amenorrhea in 25%). Of those with clinical signs, 46% had acne, and 42.5% had a family history of PCOS or infertility. 48% cited marital or family strain, and nearly half (47.5%) reported a lower quality of life. There was no statistically significant correlation (p = 0.209) between the length of infertility and BMI. Conclusion: According to the study, PCOS significantly contributes to primary infertility in Quetta among women between the ages of 25 and 30. The burden of PCOS-related reproductive difficulties in this population is highlighted by the high prevalence of sonographic and clinical characteristics. Improving fertility and quality of life requires early diagnosis, lifestyle changes, and effective management techniques.